Ecocriminological analysis of brine in aquatic ecosystems: impacts on Posidonia oceanica and the search for restorative justice solutions [version 2; peer review: 1 approved, 3 approved with reservations] - Esteban Morelle-Hungría; Pablo Serra (Open Research Europe, 2024)
The consumption of fresh water has generated additional problems in certain territories, along with the consequences of global warming. This has meant that in the most vulnerable areas, such as the Balearic archipelago in the Mediterranean, alternative water supply systems have been established: desalination plants. However, the ecological impact of these infrastructures is great, mainly affecting aquatic ecosystems. In light of the above, this paper addresses the ecological harm caused by desalination and brine discharges on a protected and priority species, P. Oceanica. Taking as ethico-legal foundation the theory of ecological justice, a multilevel analysis was carried out from an ecocriminology perspective on the impacts of this authorized practice on P. Oceanica and other species. Finally, a restorative justice view will allow us to understand and envision possible solutions to this ecological harm.